Exploring the Potentiality of Family Resources on Basic Household Sanitation Management in Dense Settlements of Binjai in North Sumatera Province of Indonesia - Naria, Evi; Santoso, Heru; Rochadi, Kintoko; Nurmaini, Nurmaini (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Community empowerment-based sanitation development by prioritizing participation has been implemented; however, it still shows insignificant progression. Even though the family is the manager of basic sanitation starting from the household, personal empowerment, and family participation miss from the focus of attention. AIM: This study thus aimed to develop a participatory model of family empowerment in the management of basic sanitation at the household level. METHODS: This type of qualitative research employed a participatory action research approach. It involved stakeholders who managed sanitation as the informants and 30 families who fulfilled the criteria namely having children over 10 years old and having no assistants as the participants. The data collection was conducted through in-depth interviews, observation, focus group discussion, and documentation. The basic sanitation includes water supply, latrines, garbage, and household waste was also examined to support the data obtained. The data were then analyzed by applying Miles and Huberman flows. RESULTS: It was found that household sanitation management was potentially implemented by managing family resources, sources of information and knowledge, motivation in family empowerment, and household sanitation support facilities. Sanitation management actions were carried out by assistance and division of tasks to family members accounting for 80%–100%. Conditions of basic sanitation in households thus were significantly better after the implementation of the sanitation management. CONCLUSION: The basic sanitation management model can be improved based on participatory family empowerment by employing assistance and the division of tasks to family members. This model also can be applied both at the local and national level and can become a guide for sustainable short or medium-term sanitation development.